2015
DOI: 10.1111/ejn.12827
|View full text |Cite
|
Sign up to set email alerts
|

Increased audiovisual integration in cochlear‐implanted deaf patients: independent components analysis of longitudinal positron emission tomography data

Abstract: It has been demonstrated in earlier studies that patients with a cochlear implant have increased abilities for audio-visual integration because the crude information transmitted by the cochlear implant requires the persistent use of the complementary speech information from the visual channel. The brain network for these abilities needs to be clarified. We used an independent components analysis (ICA) of the activation (H2(15)O) positron emission tomography data to explore occipito-temporal brain activity in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 52 publications
5
30
0
Order By: Relevance
“…These results find support in the neuroimaging literature showing different patterns of visual activation in postlingually deafened adult cochlear implant (CI) users (Strelnikov et al 2015; see Bergeson and Pisoni 2004, for behavioral studies involving CI users). In a PositronEmission-Tomography (PET) study, Strelnikov et al (2015) compared occipital-temporal activation patterns in three groups of listeners in an audiovisual speech perception task: normal-hearing listeners, recently implanted CI users, and CI users that had been implanted several months prior.…”
Section: Visual Dominant Responsessupporting
confidence: 73%
See 4 more Smart Citations
“…These results find support in the neuroimaging literature showing different patterns of visual activation in postlingually deafened adult cochlear implant (CI) users (Strelnikov et al 2015; see Bergeson and Pisoni 2004, for behavioral studies involving CI users). In a PositronEmission-Tomography (PET) study, Strelnikov et al (2015) compared occipital-temporal activation patterns in three groups of listeners in an audiovisual speech perception task: normal-hearing listeners, recently implanted CI users, and CI users that had been implanted several months prior.…”
Section: Visual Dominant Responsessupporting
confidence: 73%
“…Control results were obtained from simulation 1 (not shown again in Fig. 3 the predictions of the interactive model that predicts the McGurk effect (Bergeson and Pisoni 2004;Dodd et al 2008;Strelnikov et al 2015). Our second round of simulations showed that systematically varying the inhibition parameter value allows the model to predict the rate of the McGurk effect within individual ASD listeners.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations